THE EFFECT OF ORBICULARIS OCULI SLING ON LATERAL CANTHUS AND LOWER LID IN UPPER BLEPHAROPLASTY - Ali, Paiwand Mahmood; Qader, Ari Raheem; Hasan, Hawree Abdulsattar (Journal of Sulaimani Medical College, 2022)
Background Upper lid blepharoplasty is one of the most commonly performed procedures in aesthetic plastic surgery, which directly affects facial rejuvenation. The periocular region is the main point of focus in routine face-toface interaction. Understanding the periorbital surgical anatomy, facial analysis, and specific change in the skin, muscle and fat with preoperative workup and a thoughtfully conceived surgical plan targeted according to the difference gives a successful outcome. Objectives This dynamic region has both functional and aesthetic influence on the face; unfortunately, this area develops ageing sooner than other regions of the face. Patient and Methods A total of 30 patients underwent upper lid blepharoplasty. In the most lateral part, the orbicularis oculi muscle was divided horizontally. The lower part was suspended to the periosteum of the orbital rim with a single stitch of the long-standing absorbable suture. The upper part overlapped over the lower part of the muscle and fixed them by a single stitch in a single stitch pant over vest fashion. Results This technique provides more youthfulness to the eye, especially at the region of lateral canthus, as it lifts the tissue superolateral. It has minimal effect on lateral canthus laxity but shows marked improvement in lateral lower lid and crowfeet; it also shows valuable improvement of lateral hooding. Conclusion The orbicularis oculi muscle suspension procedure is a good technique that reliably corrects and reshapes the outer portion of both upper and lower eyelids. It is an easy technique, and it would be helpful as an adjunctive procedure with blepharoplasty in selected cases
Keywords: Blepharoplasty; Orbicularis muscle; Crow’s feet; Lateral hooding; Lateral canthus